Masyarakat Pulau Di Utara Jawa Dan Pasang Surut Budayanya - Lucas Partanda Koestoro (Balai Arkeologi Yogyakarta, 1995)
Entering the twentieth century, there was a discussion on the nautical aspects of Indonesian culture. JC van Leur started to discuss the maritime nations in the